Anti-fog self-cleaning glass based on cellulose ether coating and preparation method thereof

By applying the coating prepared by modified cellulose ether on the glass surface, the problem of uneven protective layer of the existing anti-fog glass coating in the polluted environment is solved, and the excellent anti-fog and anti-fog effect on the glass surface is achieved, and the maintenance of the glass surface is maintained. Stable anti-fog performance.

CN119059739BActive Publication Date: 2025-02-07SHANDONG HEAD GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411577836.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-07
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing anti-fog glass coating is difficult to maintain a uniform protective layer in a polluted environment, resulting in limited and uneven anti-fog effect. Under the corrosion of the external environment, the surface roughness of the coating increases, resulting in deterioration of anti-fog performance.

Method used

Using a cellulose ether-based coating, a fluorine-containing mesh compound is formed by a preparation method of modified cellulose ether, which imparts excellent anti-fog properties and self-cleaning effect to the glass surface.

Benefits of technology

It achieves uniform anti-fog and anti-fog effect on the glass surface, has stable anti-fog performance, and maintains good light transmittance after acid-base corrosion.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to an anti-fog self-cleaning glass based on a cellulose ether coating and a preparation method, and belongs to the technical field of glass coatings. The cellulose ether coating comprises, by weight, 100 parts of tetraethyl orthosilicate, 9-12 parts of an active crosslinking agent, 16-24 parts of a modified cellulose ether, 3.2-4.5 parts of nano-silicon dioxide, 0.4-0.5 parts of a leveling agent, and 0.2-0.3 parts of a defoaming agent; the modified cellulose ether uses hydroxypropyl methylcellulose as a raw material, is alkalized by sodium hydroxide, is substituted by an alkyl glycol and trifluoropropylmethyldichlorosilane, and is terminated with an alcohol hydroxyl group, that is, a fluorinated intermediate is obtained, and then the end hydroxyl group of the fluorinated intermediate is opened by epichlorohydrin, and then the ring is closed under the promotion of strongly alkaline potassium tert-butoxide, and epoxy modification is introduced into the end of the fluorinated intermediate, that is, an epoxy modifier is obtained, and the modified cellulose ether is uniformly enriched on the surface during the coating forming process to form a stable protective layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass coatings, and in particular relates to an anti-fog self-cleaning glass based on a cellulose ether coating and a preparation method thereof. Background Art

[0002] Glass-like transparent materials are widely used in all aspects of daily life, transportation, and medical treatment. The widespread use of glass-like transparent materials makes production and life more convenient and is an indispensable part of our production and life. However, when the humidity and temperature of the environment in which the glass-like materials are located change, fog will appear on its surface, seriously affecting the use and appearance of the glass. For example, when there is a large temperature difference between indoors and outdoors, a layer of fog will immediately appear on the surface of glasses when entering indoors from outdoors, which will greatly affect people's experience; fogged windshields and rearview mirrors will interfere with people's vision, thus posing a hidden danger; fog on the surface of doctors' goggles, protective masks, and surgical endoscopes will affect doctors' operations and may even cause medical accidents; therefore, research in the field of anti-fog technology has attracted more and more attention.

[0003] There are many anti-fog methods currently in use, which can be divided into two categories. One is to change the parameters of the surface environment of glass-like transparent materials to heat the substrate to increase the surface temperature or speed up the air flow rate on the surface so that the water droplets reach above the dew point without condensing. Speeding up the air flow rate on the surface will speed up the evaporation of water droplets and reduce the humidity to achieve the anti-fog effect. However, this anti-fog method consumes additional energy and requires special design according to different equipment; the other is to change the affinity between the solid surface and the droplets by modifying the surface of the material, so that the glass surface reaches high hydrophilicity or high hydrophobicity to achieve the purpose of anti-fog. Compared with the first type of anti-fog, The method requires additional energy costs, while the second type of anti-fog method is more ideal and economical. Among them, the highly hydrophilic anti-fog method has high limitations, especially in an environment with many pollutants, it is very easy to cause pollution accumulation and the water film cannot be evenly spread, while the highly hydrophobic method can have both anti-fog and anti-fouling effects and is more applicable. At present, the more mature and economical technical means is mainly the coating method, which composites a hydrophobic coating on the glass surface to achieve the anti-fog purpose. However, it is difficult for the hydrophobic component to form a uniform protective layer on the coating surface, resulting in limited anti-fog effect, and the uneven hydrophobic component causes uneven surface quality of the coating. Under the corrosion of the external environment, the surface roughness of the coating increases, which makes the anti-fog performance deteriorate sharply. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide an anti-fog self-cleaning glass based on cellulose ether coating and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A cellulose ether coating-based anti-fog self-cleaning glass, wherein the cellulose ether coating comprises the following raw materials in parts by weight: 100 parts of tetraethyl orthosilicate, 9-12 parts of an active crosslinking agent, 16-24 parts of modified cellulose ether, 3.2-4.5 parts of nano-silicon dioxide, 0.4-0.5 parts of a leveling agent, and 0.2-0.3 parts of a defoaming agent;

[0007] The modified cellulose ether is prepared by the following method:

[0008] Step A1: Alkyl glycol, triethylamine and tetrahydrofuran are mixed, dry nitrogen is introduced for protection, the temperature is raised to 45-60°C, stirring is applied at 90-150 rpm, trifluoropropylmethyldichlorosilane is slowly added and reacted for 3.8-5.5 hours, and tetrahydrofuran is removed by rotary evaporation after the reaction is completed to obtain a fluorinated intermediate;

[0009] Further, the feed ratio of trifluoropropylmethyldichlorosilane, alkyl glycol, triethylamine and tetrahydrofuran is 10mmol:13-16mmol:1-1.5mL:25-40mL, and the excess alkyl glycol is substituted with trifluoropropylmethyldichlorosilane and terminated with alcoholic hydroxyl groups to form a chain compound with a small molecular weight;

[0010] Preferably, the alkyl diol is selected from one of 1,8-octanediol, 1,10-decanediol and 1,12-dodecanediol. The fluorinated intermediate prepared under the alkyl chain length has a moderate molecular weight and is easy to carry out subsequent reactions.

[0011] Step A2: Mix the fluorinated intermediate, epichlorohydrin and acetone, raise the temperature to 55-60°C, apply stirring at 60-90 rpm, reflux for 2.5-3.5 hours, then add potassium tert-butoxide and continue the reaction for 5-8 hours. After the reaction is completed, remove the acetone by rotary evaporation, wash the substrate with water, remove the aqueous phase and vacuum dry to obtain an epoxy modifier;

[0012] Furthermore, the feed ratio of the fluorinated intermediate, epichlorohydrin, potassium tert-butoxide and acetone is 10g:1.2-1.6mL:0.15-0.2g:15-22mL, epichlorohydrin and the end hydroxyl group of the fluorinated intermediate are ring-opened, and then the ring is closed under the promotion of the strong alkaline potassium tert-butoxide, and the epoxy group modification is introduced into the end of the fluorinated intermediate.

[0013] Step A3: Add hydroxypropyl methylcellulose and dioxane and heat to 50-60°C to mix, add sodium hydroxide aqueous solution to mix, continue to heat to 90-100°C and reflux for 3-4h, evaporate to dryness under reduced pressure after the reaction is completed, and obtain alkalized cellulose;

[0014] Furthermore, the feed ratio of hydroxypropyl methylcellulose, sodium hydroxide and dioxane is 10g:1.8-2.2g:30-40mL, the mass fraction of the sodium hydroxide aqueous solution is 15%, and the sodium hydroxide acts on the hydroxyl groups in the hydroxypropyl methylcellulose molecules to form sodium cellulose.

[0015] Step A4: Alkalized cellulose, epoxy modifier, anhydrous sodium sulfate and dimethylformamide are mixed, first heated to 110-130° C., stirred at 60-90 rpm, and refluxed for 6-8 hours. After the reaction is completed, dimethylformamide is removed by fumigation under reduced pressure to obtain modified cellulose ether;

[0016] Furthermore, the feed ratio of alkalized cellulose, epoxy modifier, anhydrous sodium sulfate and dimethylformamide is 10g: 0.8-1.4g: 0.1-0.15g: 18-25mL, and the epoxy modifier and alkalized cellulose are etherified at high temperature to form a network etherified product of epoxy modifier-bridged cellulose molecules.

[0017] Preferably, the active crosslinking agent is selected from γ-glycidyloxypropyltrimethoxysilane.

[0018] A method for preparing anti-fog self-cleaning glass based on cellulose ether coating comprises the following steps:

[0019] Step S1: premix the raw materials, add ethanol solution to adjust the viscosity to 3000 cP, and perform vacuum degassing to obtain a composite coating;

[0020] Step S2: Scrape the composite coating onto the surface of the substrate glass, pre-bake at 60° C. for 1 hour, then heat to 120° C. and bake to cure for 3 hours to obtain anti-fog self-cleaning glass.

[0021] Beneficial effects of the present invention:

[0022] The invention discloses a silicon-based coating for glass surface, which takes tetraethyl orthosilicate as a main film-forming material and is compounded with a modified cellulose ether independently developed, so as to give the glass surface excellent anti-fogging property and self-cleaning effect; the modified cellulose ether takes hydroxypropyl methylcellulose as a raw material, is subjected to alkalization treatment by sodium hydroxide, is substituted by alkyl glycol and trifluoropropyl methyldichlorosilane and is terminated with alcohol hydroxyl groups to form a chain compound with a small molecular weight, that is, a fluorinated intermediate is obtained, and then the end hydroxyl groups of the fluorinated intermediate are opened by epichlorohydrin and the fluorinated intermediate is closed by the promotion of strongly alkaline potassium tert-butoxide, and an epoxy group is introduced into the end of the fluorinated intermediate for modification, that is, an epoxy modifier is obtained, and finally, the epoxy modifier and the alkalized cellulose are etherified at high temperature to obtain a fluorinated intermediate. Modified cellulose ether; the modified cellulose ether uses cellulose long chains as a base material and epoxy modifiers as a bridging material to form a fluorine-containing network compound, and the fluorine structure between the fiber chains modifies it to impart good tolerance and hydrophobic anti-fouling properties; during the coating forming process, the fluorine structure produces a segregation effect, so that the network-like modified cellulose ether spreads on the surface of the coating. Different from small molecule fluorine-containing additives, the cellulose is open to form constraints on the fluorine structure, and the network structure is uniformly enriched to the surface, making the coating surface quality more uniform. At the same time, the cellulose chain forms a supporting effect, so that the surface fluorine structure presents a relatively orderly spatial distribution, avoiding excessive enrichment of the surface fluorine structure leading to deterioration of the coating surface performance, so that the coating has a stable anti-fog self-cleaning protective effect. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1, preparation of anti-fog self-cleaning glass based on cellulose ether coating, the specific implementation process is as follows:

[0025] (1) Preparation of modified cellulose ether

[0026] Step A1: Take an alkyl glycol, triethylamine and tetrahydrofuran, mix them, pass dry nitrogen protection, heat to 45°C, stir at 90rpm, slowly add trifluoropropylmethyldichlorosilane and react for 3.8h, wherein the alkyl glycol is selected from 1,8-octanediol, and the feed ratio of trifluoropropylmethyldichlorosilane, alkyl glycol, triethylamine and tetrahydrofuran is 10mmol:13mmol:1mL:25mL. After the reaction, remove tetrahydrofuran by rotary evaporation to obtain a fluorinated intermediate.

[0027] Step A2: Mix the fluorinated intermediate, epichlorohydrin and acetone, heat to 55°C, stir at 60 rpm, reflux for 3.5 hours, then add potassium tert-butoxide and continue the reaction for 5 hours, wherein the feed ratio of the fluorinated intermediate, epichlorohydrin, potassium tert-butoxide and acetone is 10 g:1.2 mL:0.15 g:15 mL. After the reaction, remove the acetone by rotary evaporation, wash the substrate with water, remove the aqueous phase and vacuum dry to obtain the epoxy modifier.

[0028] Step A3: Take hydroxypropyl methylcellulose and dioxane as feed materials and heat to 50°C to mix, add sodium hydroxide aqueous solution to mix, continue to heat to 90°C and reflux for 4 hours, wherein hydroxypropyl methylcellulose is selected from HT-E type raw material, the mass fraction of sodium hydroxide aqueous solution is 15%, and the feed ratio of hydroxypropyl methylcellulose, sodium hydroxide and dioxane is 10g:1.8g:30mL. After the reaction is completed, evaporate to dryness under reduced pressure to obtain alkalized cellulose.

[0029] Step A4: Take alkalized cellulose, epoxy modifier, anhydrous sodium sulfate and dimethylformamide, mix them, first heat them to 110°C, stir them at 60rpm, and reflux them for 8h, wherein the feed ratio of alkalized cellulose, epoxy modifier, anhydrous sodium sulfate and dimethylformamide is 10g:0.8g:0.1g:18mL. After the reaction is completed, dimethylformamide is removed by reduced pressure fumigation to obtain modified cellulose ether.

[0030] (2) Preparation of anti-fog self-cleaning glass

[0031] Step S1: taking raw materials by weight, 100 parts of tetraethyl orthosilicate, industrial-grade raw material; 9 parts of active crosslinking agent, selected from γ-glycidyloxypropyltrimethoxysilane, industrial-grade raw material; 16 parts of modified cellulose ether, prepared in this embodiment; 4.5 parts of nano-silicon dioxide, selected from Brofos-SiO2-H20 type raw material, with an average particle size of 20 nm; 0.5 parts of leveling agent, selected from KMT-5502 type raw material; 0.2 parts of defoaming agent, selected from KMT-7033 type raw material; adding each raw material into a mixer, stirring at 30 rpm, slowly adding 60% by volume ethanol solution to adjust the viscosity of the mixture to 3000 cP, vacuum degassing for 10 minutes, and obtaining a composite coating;

[0032] Step S2: Apply the composite coating on the surface of the substrate glass with a coating amount of 35 g / m 2 , placed in an oven, pre-baked at 60°C for 1 hour, then heated to 120°C and baked for curing for 3 hours to obtain anti-fog self-cleaning glass.

[0033] Example 2, preparation of anti-fog self-cleaning glass based on cellulose ether coating, the specific implementation process is as follows:

[0034] (1) Preparation of modified cellulose ether

[0035] Step A1: Take an alkyl glycol, triethylamine and tetrahydrofuran, mix them, pass dry nitrogen protection, heat to 60°C, stir at 150rpm, slowly add trifluoropropylmethyldichlorosilane and react for 5.5h, wherein the alkyl glycol is selected from 1,12-dodecanediol, and the feed ratio of trifluoropropylmethyldichlorosilane, alkyl glycol, triethylamine and tetrahydrofuran is 10mmol:16mmol:1.5mL:40mL. After the reaction, remove tetrahydrofuran by rotary evaporation to obtain a fluorinated intermediate.

[0036] Step A2: Mix the fluorinated intermediate, epichlorohydrin and acetone, raise the temperature to 60°C, stir at 90 rpm, reflux for 2.5 hours, then add potassium tert-butoxide and continue the reaction for 8 hours, wherein the feed ratio of the fluorinated intermediate, epichlorohydrin, potassium tert-butoxide and acetone is 10 g:1.6 mL:0.2 g:22 mL. After the reaction, remove the acetone by rotary evaporation, wash the substrate with water, remove the aqueous phase and vacuum dry to obtain the epoxy modifier.

[0037] Step A3: Take hydroxypropyl methylcellulose and dioxane as feed materials and heat them to 60°C to mix, add sodium hydroxide aqueous solution to mix, continue to heat to 100°C and reflux for 3h, wherein hydroxypropyl methylcellulose is selected from HT-E type raw material, the mass fraction of sodium hydroxide aqueous solution is 15%, and the feed ratio of hydroxypropyl methylcellulose, sodium hydroxide and dioxane is 10g:2.2g:40mL. After the reaction is completed, evaporate to dryness under reduced pressure to obtain alkalized cellulose.

[0038] Step A4: Take alkalized cellulose, epoxy modifier, anhydrous sodium sulfate and dimethylformamide, mix them, first heat them to 130°C, stir them at 90rpm, and reflux them for 6h, wherein the feed ratio of alkalized cellulose, epoxy modifier, anhydrous sodium sulfate and dimethylformamide is 10g:1.4g:0.15g:25mL. After the reaction is completed, dimethylformamide is removed by reduced pressure fumigation to obtain modified cellulose ether.

[0039] (2) Preparation of anti-fog self-cleaning glass

[0040] Step S1: taking raw materials by weight, 100 parts of tetraethyl orthosilicate, industrial-grade raw material; 12 parts of active crosslinking agent, selected from γ-glycidyloxypropyltrimethoxysilane, industrial-grade raw material; 24 parts of modified cellulose ether, prepared in this embodiment; 3.2 parts of nano-silicon dioxide, selected from Brofos-SiO2-H20 type raw material, with an average particle size of 20 nm; 0.4 parts of leveling agent, selected from KMT-5502 type raw material; 0.3 parts of defoaming agent, selected from KMT-7033 type raw material; adding each raw material into a mixer, stirring at 30 rpm, slowly adding 60% by volume ethanol solution to adjust the viscosity of the mixture to 3000 cP, vacuum degassing for 10 minutes, and obtaining a composite coating;

[0041] Step S2: Apply the composite coating on the surface of the substrate glass with a coating amount of 35 g / m 2 , placed in an oven, pre-baked at 60°C for 1 hour, then heated to 120°C and baked for curing for 3 hours to obtain anti-fog self-cleaning glass.

[0042] Example 3, preparation of anti-fog self-cleaning glass based on cellulose ether coating, the specific implementation process is as follows:

[0043] (1) Preparation of modified cellulose ether

[0044] Step A1: Take an alkyl glycol, triethylamine and tetrahydrofuran, mix them, pass dry nitrogen protection, heat to 55°C, apply stirring at 120rpm, slowly add trifluoropropylmethyldichlorosilane and react for 4.5h, wherein the alkyl glycol is selected from 1,10-decanediol, and the feed ratio of trifluoropropylmethyldichlorosilane, alkyl glycol, triethylamine and tetrahydrofuran is 10mmol:15mmol:1.3mL:35mL. After the reaction, remove tetrahydrofuran by rotary evaporation to obtain a fluorinated intermediate.

[0045] Step A2: Mix the fluorinated intermediate, epichlorohydrin and acetone, heat to 60°C, stir at 90 rpm, reflux for 3 hours, then add potassium tert-butoxide and continue the reaction for 6 hours, wherein the feed ratio of the fluorinated intermediate, epichlorohydrin, potassium tert-butoxide and acetone is 10 g:1.4 mL:0.18 g:20 mL. After the reaction, remove the acetone by rotary evaporation, wash the substrate with water, remove the aqueous phase and dry in vacuo to obtain an epoxy modifier.

[0046] Step A3: Take hydroxypropyl methylcellulose and dioxane as feed materials and heat to 55°C to mix, add sodium hydroxide aqueous solution to mix, continue to heat to 100°C and reflux for 3.5h, wherein hydroxypropyl methylcellulose is selected from HT-E type raw material, the mass fraction of sodium hydroxide aqueous solution is 15%, and the feed ratio of hydroxypropyl methylcellulose, sodium hydroxide and dioxane is 10g:2g:35mL. After the reaction is completed, evaporate to dryness under reduced pressure to obtain alkalized cellulose.

[0047] Step A4: Take alkalized cellulose, epoxy modifier, anhydrous sodium sulfate and dimethylformamide, mix them, first heat them to 120°C, stir them at 90rpm, and reflux them for 6.5h, wherein the feed ratio of alkalized cellulose, epoxy modifier, anhydrous sodium sulfate and dimethylformamide is 10g:1.1g:0.12g:22mL. After the reaction is completed, dimethylformamide is removed by reduced pressure fumigation to obtain modified cellulose ether.

[0048] (2) Preparation of anti-fog self-cleaning glass

[0049] Step S1: taking raw materials by weight, 100 parts of tetraethyl orthosilicate, industrial-grade raw material; 10 parts of active crosslinking agent, selected from γ-glycidyloxypropyltrimethoxysilane, industrial-grade raw material; 20 parts of modified cellulose ether, prepared in this embodiment; 3.8 parts of nano-silicon dioxide, selected from Brofos-SiO2-H20 type raw material, with an average particle size of 20 nm; 0.4 parts of leveling agent, selected from KMT-5502 type raw material; 0.3 parts of defoaming agent, selected from KMT-7033 type raw material; adding each raw material into a mixer, stirring at 30 rpm, slowly adding 60% by volume ethanol solution to adjust the viscosity of the mixture to 3000 cP, vacuum degassing for 10 minutes, and obtaining a composite coating;

[0050] Step S2: Apply the composite coating on the surface of the substrate glass with a coating amount of 35 g / m 2 , placed in an oven, pre-baked at 60°C for 1 hour, then heated to 120°C and baked for curing for 3 hours to obtain anti-fog self-cleaning glass.

[0051] Comparative Example 1, referring to Example 3, the modified cellulose ether was replaced by 18 parts of HD10W hydroxyethyl cellulose ether and 2 parts of perfluorooctyl triethoxysilane, and the rest of the implementation process was exactly the same.

[0052] Comparative Example 2: A commercially available YCP0051KT hydrophobic and oleophobic coating was selected and cured at room temperature for 24 hours after scraping to obtain an anti-fog self-cleaning glass.

[0053] Samples were taken from the materials prepared as above, and the adhesion of the coating was tested according to GB / T 9286-2021, and the water contact angle of the coating was tested according to GB / T 24368-2009. The light transmittance of the sample at a wavelength of 380-1100nm was tested using an air-floating tabletop spectral transmittance measurement system, which was recorded as T0. The specific test results are shown in Table 1:

[0054] Table 1:

[0055] ,

[0056] It can be seen from the test results in Table 1 that the glass coating prepared in the embodiment has good adhesion, the surface water contact angle is higher than 120°, it is not easy to be contaminated, it can be self-cleaned under washing by rain water, etc., and the glass maintains good light transmittance.

[0057] The sample was fumigated above 90℃ hot water for 1min, and the light transmittance test was performed again, which was recorded as T1. The anti-fog performance was measured by the light transmittance loss rate, and the anti-fog light transmittance loss rate = (T0-T1) / T0×100%; the sample was immersed in 5% hydrochloric acid and 5% sodium hydroxide solution for 24h, respectively, and after cleaning, it was fumigated again and the light transmittance test was performed, which were recorded as T2 and T3 respectively. The acid-resistant light transmittance loss rate = (T0-T2) / T0×100%, and the alkali-resistant light transmittance loss rate = (T0-T3) / T0×100% were calculated. The specific test results are shown in Table 2:

[0058] Table 2:

[0059] ,

[0060] It can be seen from the test results in Table 2 that the anti-fog light transmission loss rates of the embodiment and comparative example 2 are both low, and have good anti-fog performance. However, after acid and alkaline corrosion, the anti-fog light transmission loss rate of comparative example 2 is high, and the anti-fog performance deteriorates.

[0061] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0062] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An anti-fog self-cleaning glass based on cellulose ether coating, characterized in that: The cellulose ether coating comprises the following raw materials in parts by weight: 100 parts of tetraethyl orthosilicate, 9-12 parts of active crosslinking agent, 16-24 parts of modified cellulose ether, 3.2-4.5 parts of nano silicon dioxide, 0.4-0.5 parts of leveling agent and 0.2-0.3 parts of defoaming agent; The modified cellulose ether is prepared by the following method: Step A1: Alkyl glycol, triethylamine and tetrahydrofuran are mixed, dry nitrogen is introduced for protection, the temperature is raised to 45-60°C, trifluoropropylmethyldichlorosilane is slowly added with stirring, and the reaction is carried out for 3.8-5.5 hours. After the reaction is completed, tetrahydrofuran is removed by rotary evaporation to obtain a fluorinated intermediate; Step A2: Mix the fluorinated intermediate, epichlorohydrin and acetone, heat to 55-60°C, stir and reflux for reaction for 2.5-3.5h, then add potassium tert-butoxide and continue the reaction for 5-8h. After the reaction is completed, remove the acetone by rotary evaporation, wash the substrate with water, remove the aqueous phase and vacuum dry to obtain an epoxy modifier; Step A3: Add hydroxypropyl methylcellulose and dioxane and heat to 50-60°C to mix, add sodium hydroxide aqueous solution to mix, continue to heat to 90-100°C and reflux for 3-4h, evaporate to dryness under reduced pressure after the reaction is completed, and obtain alkalized cellulose; Step A4: Alkalized cellulose, epoxy modifier, anhydrous sodium sulfate and dimethylformamide are mixed, first heated to 110-130° C., stirred and refluxed for reaction for 6-8 hours, and after the reaction is completed, dimethylformamide is removed by vacuum fumigation to obtain modified cellulose ether.

2. The anti-fog self-cleaning glass based on cellulose ether coating according to claim 1, characterized in that: The feed ratio of trifluoropropylmethyldichlorosilane, alkyl glycol, triethylamine and tetrahydrofuran is 10 mmol: 13-16 mmol: 1-1.5 mL: 25-40 mL.

3. The anti-fog self-cleaning glass based on cellulose ether coating according to claim 2, characterized in that: The alkyl diol is one of 1,8-octanediol, 1,10-decanediol and 1,12-dodecanediol.

4. The anti-fog self-cleaning glass based on cellulose ether coating according to claim 2, characterized in that: The feed ratio of the fluorinated intermediate, epichlorohydrin, potassium tert-butoxide and acetone is 10 g: 1.2-1.6 mL: 0.15-0.2 g: 15-22 mL.

5. The anti-fog self-cleaning glass based on cellulose ether coating according to claim 4, characterized in that: The feed ratio of hydroxypropyl methylcellulose, sodium hydroxide and dioxane is 10g:1.8-2.2g:30-40mL.

6. The anti-fog self-cleaning glass based on cellulose ether coating according to claim 5, characterized in that: The feed ratio of alkalized cellulose, epoxy modifier, anhydrous sodium sulfate and dimethylformamide is 10g: 0.8-1.4g: 0.1-0.15g: 18-25mL.

7. The anti-fog self-cleaning glass based on cellulose ether coating according to claim 1, characterized in that: The active crosslinking agent is γ-glycidyloxypropyltrimethoxysilane.

8. A method for preparing anti-fog self-cleaning glass based on cellulose ether coating according to any one of claims 1 to 7, characterized in that: The steps include: Step S1: premix the raw materials, add ethanol solution to adjust the viscosity to 3000 cP, and perform vacuum degassing to obtain a composite coating; Step S2: Scrape the composite coating onto the surface of the substrate glass, pre-bake at 60° C. for 1 hour, then heat to 120° C. and bake to cure for 3 hours to obtain anti-fog self-cleaning glass.

Citation Information

Patent Citations

  • Transparent Anti-fog coating

    CA2178525A1

  • Preparation method of oriented hydrophobic modified cellulose

    CN117343202A